PEMBELAJARAN RANTAI MAKANAN MELALUI MEDIA PAPER RONAN UNTUK MENINGKATKAN LITERASI SAINS KELAS V SEKOLAH DASAR - Hartini, Sri Hastuti Anwa; Wuryaningrum, Rusdhianti; Sudarti, Sudarti (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to determine the effect of the Food Wheel Rotation Board Media (Paper Ronan) on Increasing Science Literacy at Class V Elementary Schools. The research method applied experimental research, in the form of a nonequivalent control group design. The sample was 19 students of class VA as the experimental class and 21 students of class VB as the control class. The data collection tool was test questions regarding scientific literacy, with data analysis techniques using the quantitative paired T test technique using SPSS. The results of this research show that there is a significant difference in the scientific literacy abilities of the experimental group compared to the control group as evidenced by the results of the hypothesis test where the tcount>ttable value is 2.120>1.683. These results provide a decision to accept Ha and reject H0. Thus, it can be concluded that there is a significant influence of the use of the Food Wheel Spinning Board (Paper Ronan) media on the Science Literacy of Class V Elementary Schools.